Pengaruh Perceived Organization Support Dan Lingkungan Kerja Terhadap Kinerja Karyawan Dimoderasi Oleh Gaya Kepemimpinan Transformasional (Studi Pada Dinas Perhubungan Sumatera Utara) - Lisma Nikmat Tarisa Marpaung; Saskia; Hafriz Rifki Hafas (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to determine whether there is an effect of Perceived Organization Support and work environment on employee performance moderated by transformational leadership style at the Department of Transportation of North Sumatra. This research is associative with a quantitative approach. sampling used is saturated sample. The sample employees in this study were 118 employees. The results of the research on the Perceived Organizational Support variable have a positive and significant effect on employee performance, there is a positive and significant effect on the work environment variable on employee performance. Perceived Organizational Support and Work Environment together have a positive and significant effect on Employee Performance. Perceived Organizational Support on Employee Performance is moderated by a significant Transformational Leadership Style. Work Environment on Employee Performance moderated by Transformational Leadership Style has a positive and significant effect